Preferences, digestibility and rumen fermentation characteristics of several mulberry species in goats - Simon Petrus Ginting; Andi Tarigan; Rijanto Hutasoit; Dwi Yulistiani (Indonesian Center for Animal Research and Development (ICARD), 2014)
This study was aimed to investigate the preferences and nutritional qualities of four mulberry species (Morus cathyana, Morus nigra, Morus indica and Morus multicaulis) in goat diet. Foliages were fed to six adult Boer x Kacang goats in a cafetaria style for preference analyses. Nutritional qualities (feed intake, apparent digestibility, N balances, rumen fermentation characteristics) and blood metabolites were measured in a digestion trial. Twenty male goats were used in a completely randomised arrangement of four treatments (mulberry species) and five replications. The selectivity indices were +0,389, -0,156, -0,154 and -0,234 for M. multicaulis, M. nigra, M. cathyana and M. indica, respectively, indicating that M. multicaulis was the most and M. indica was the least preferred species. When fed as the sole foliage the DM intake was higher (P<0.05) in goats offered M. multicaulis (780 g/d) and M. nigra (718 g/d) compared to those fed M. cathyana (637 g/d) and M. indica (598 g/d). The DM intake were equal to 38.6; 35.5; 31.5 dan 29.6 g/kg BW, respectively. The DM apparent digestibility were not different (P>0.05) among the species ranging from 60-65%. The N balances (N retained) was highest (P<0.05) in the M. multicaulis group (16,7 g/d) and was lowest in the M. indica (12,3 g/d) and M. cathyana groups (11,7 g/d). The rumen pH and total VFA concentration was not diferent (P>0,05) among treatments. The ammonia concentration was higest (P>0,05) in the M. multicaulis and was lowest in the M. indica and M. cathyana groups. The bacteria and protozoa population was not different (P>0,05) among the treatments. It is concluded that M. multicaulis was more preferred by goats compared to M. nigra, M. indica and M. cathyana, but all species have potential as foliages for goats as shown by its high intake, digestibility and rumen fermentation rates.